Family Support For Compliance with Medication in Schizophrenia - Fauziah, Sifa; Balqis, Ummi Malikal; Umaiyah, Siti (Jurnal Keperawatan, 2024)
Schizophrenia cannot be defined as a separate disease, but is thought to be a syndrome or disease process that includes many types with various symptoms. Family support is assistance that can be given to other family members in the form of goods, services, information and advice that can make the support recipient feel loved, appreciated and at peace. The family provides support, attention and affection by caring for, administering treatment and controlling medication intake for mental disorders patients. This study aims to determine the relationship between family support and medication adherence for mental disorder patients. This research uses a quantitative research design with a cross sectional approach. The population in this study were patients with schizophrenia in the working area of the Karang Tengah Community Health Center. Samples were collected using a total sampling technique, namely 35 people. Data were collected using the family support questionnaire (KDK) and the Morisky Medication Adhrence Scale-8 (MMAS-8) questionnaire with an r table value of 0.056. The data was then analyzed using the chi square test (α<0.05). From the results of the bivariate chi square analysis statistical test, the p-value = 0.002 or p <0.05 was obtained. Conclusion: H0 is rejected and H1 is accepted, thus indicating that there is a relationship between family support and medication adherence in schizophrenia. Suggestion: It is hoped that the family can provide optimal support to the patient, always controlling their treatment/taking the medicines that have been prescribed.